Designing a proposed educational program based on (Gilbert-Neff) theory to decrease self-abasement for Mosul university students - AlKhalidi, Fatin Zaki; AlAbaji, Nada Fattah (Edelweiss Applied Science and Technology, 2025)
The goal of the current study is to develop a program that reduces self-abasement in accordance with Gilbert-Neff theory. To this end, the researchers created twenty lessons that address self-compassion, including mental alertness versus excessive autism, common humanity versus isolation, and self-kindness versus self-judgment. The program was submitted to a committee of 22 specialists in order to gauge its authenticity. For the academic year 2023–2024, the researchers ran a pilot study with thirty male and female students at Mosul University. This experiment aimed to determine the degree of instructional clarity, the amount of time needed for each lecture, and the main difficulties the researchers encountered when delivering the program. Twenty-four colleges at Mosul University make up the population of the study. The College of Basic Education (also known as the Department of Kindergarten) was chosen as the study's sample because its students displayed the highest level of self-abasement among the colleges at Mosul University. The outcome of the research was the creation of the program's final form, and the researchers' suggestions included the following: In order to help the students develop self-compassion, the researchers created a program. The program is used as part of the guiding efforts by the unit of educational guidance and psychological direction. The researchers recommend conducting a study to adapt the program to additional stages.